A child with pica. A case presentation. - Lidia Rosa Pérez González; Yanelis La Rosa Linares; Mariela Silverio Mesa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
This is a case of a 4 year old child who was brought to the provincial Pediatric Hospital because of faecal stones. Iron deficit and intestinal parasites were found . The patient received treatment for 6 months till the ingestion of stones disappeared with the control of the etiologic factors that caused it.